The Learning Management of Collaborative Learning along with KWDL Technique to Enhance Mathematical Word Problem-Solving Ability and Collaborative Learning Skills for Primary 4 (Grade 4) Students - Sunisa Suriyachote, Saiphin Siharak (International Journal of Advanced Science and Technology, 2020)
The purposes of this research were: 1) to compare the ability to solve mathematical problems of primary 4 (grade 4) students between who received learning by using traditional method and who learning by using collaborative learning along with KWDL techniques, and 2) to compare the collaborative learning skills of primary 4 (grade 4) students between who received learning by using traditional method and who learning management by using collaborative learning along with KWDL technique. The samples were composed of primary 4 (grade 4) students in Bueng Ba School in the second semester of the academic year 2019, which were randomly assigned into an experimental group and a control group of 2 classrooms. The research instruments consisted of 5 activity plans learning by using collaborative learning along with KWDL techniques on addition, subtraction, multiplication, and division, activity plans to organize learning activities using traditional methods, test of ability to solve mathematical problems, and the assessment test for the collaborative learning skill test. The result of the research showed that: 1) the ability in solving mathematical problems of students who study by using collaborative learning along with KWDL technique were higher than the students who received learning by using traditional method with statistical significance at the level of .05. and 2) the collaborative learning skills of students who study by using collaborative learning along with KWDL techniques were higher than students who are learning by traditional method with statistical significance at the level of .05.